Grand challenges in marine governance for ocean sustainability in the twenty-first century - Ferse, Sebastian C. A. (Frontiers in Ocean Sustainability, 2023)
The 21st century is seeing multiple and accelerating anthropogenic threats to the Ocean which jeopardize the planetary system and human well-being. Given the urgency of this planetary emergency, ensuring Ocean sustainability and an equitable and just future for humanity and the planet requires unprecedented acceleration and innovation in the theory and practice of marine governance. This Perspective provides an overview of recent trends and emerging issues facing the Ocean. It outlines a number of Grand Challenges, or important areas to advance for scholars and practitioners of marine governance, namely the bridging of sectors and scales, connecting people and the seas, consideration of inclusivity, equity and justice, and innovating knowledge generation and the interface of science, society and policy. This will allow to address questions of how to achieve just, equitable and sustainable use of and interaction with the Ocean in the 21st century.